Gender Differences in Concerns for the Environment Among the Chinese Public: An Update. Issue 6 (3rd June 2017) - Xiao, Chenyang; Hong, Dayong
ABSTRACT: Research in China seems to find stronger men's than women's environmental concern, unlike what is commonly found in the West. Such findings thus raise questions of the cross-cultural applicability of the existing theories of gendered pattern of environmental concern that have originated in the West. This current study uses data from the 2010 Chinese General Social Survey to provide an update to this research. Results show that in contemporary China women generally are no longer less concerned about the environment than Chinese men, even though women's lower environmental knowledge somewhat hinders their overall levels of environmental concern. In fact, with equal environmental knowledge, Chinese women are slightly more concerned about environmental problems, consistent with the literature in the West. This current study therefore suggests that relevant theories from the West may likely be applicable to the case of China after all.